Endometriosis and Cardiovascular Disease: A Systematic Review - Pande Putu Firsta Widyaning (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2024)
Introduction: Endometriosis is a chronic condition characterized by the aberrant distribution of functional tissue outside of the uterus, such as endometrial ducts and stroma. It is dependent on estrogen. Cardiovascular disease may be more prevalent in women who have endometriosis. Materials/Methods: Using the following keywords: